2016
DOI: 10.1021/acs.jcim.5b00638
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Interfacial Hydration Networks of Target–Ligand Complexes

Abstract: Interfacial hydration strongly influences interactions between biomolecules. For example, drug-target complexes are often stabilized by hydration networks formed between hydrophilic residues and water molecules at the interface. Exhaustive exploration of hydration networks is challenging for experimental as well as theoretical methods due to high mobility of participating water molecules. In the present study, we introduced a tool for determination of the complete, void-free hydration structures of molecular i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(88 citation statements)
references
References 72 publications
4
77
0
7
Order By: Relevance
“…This approach is successful because it implicitly contains all changes in binding site water distribution and hydrogen bond formation without the need of their explicit analysis. It was shown that an analysis with the tool MobyWat , based on evaluation of solvent MD simulation on short time scales, provides a relatively simple access to the mobile water positional network on the protein surface . In Sf6TSP, however, this method could not distinguish water networks between the different mutants (Figure S9), emphasizing the need for further mathematical algorithms to solvent network analysis…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach is successful because it implicitly contains all changes in binding site water distribution and hydrogen bond formation without the need of their explicit analysis. It was shown that an analysis with the tool MobyWat , based on evaluation of solvent MD simulation on short time scales, provides a relatively simple access to the mobile water positional network on the protein surface . In Sf6TSP, however, this method could not distinguish water networks between the different mutants (Figure S9), emphasizing the need for further mathematical algorithms to solvent network analysis…”
Section: Discussionmentioning
confidence: 99%
“…The tool for clustering structures g _ cluster by GROMACS4.6.4 was used to derive ligand clusters. Water positional analysis was performed using MobyWat as described previously . Hydrogen bond occupancies were scaled between individual complexes by summing up all hydrogen bond occupancies above a threshold of 10 % and by normalizing this sum to 1.0 for the Sf6TSP reference.…”
Section: Methodsmentioning
confidence: 99%
“…Our comparison of the crystal structure of T. maritima SecA containing the 50 aa CSI with its homology model lacking the 50 aa CSI has revealed that a number of water molecules form an intermediate interaction between the residues from this CSI and ADP molecule. Although the roles of conserved water molecules in mediating protein-ligand interactions have been increasingly recognized in recent years [76,[78][79][80][89][90][91][92], our understanding of the significance of these conserved waters in SecA, or how other sequence features of the protein contribute towards their conservation, is limited. To investigate this aspect, molecular dynamics (MD) simulations were carried out to examine the structural dynamics of the 50 aa CSI in SecA protein and the water molecules found in its proximity in the crystal structure of TmSecA at two different temperatures (303.15 K, and 363.15 K).…”
Section: Discussionmentioning
confidence: 99%
“…The tool for clustering structures g_cluster by GROMACS4.6.4 was used to derive ligand clusters. Water positional analysis was performed using MobyWat 51,52 as described previously. 27 Hydrogen bond occupancies were scaled between individual complexes by summing up all hydrogen bond occupancies above a threshold of 10 % and by normalizing this sum to 1.0 for the Sf6TSP reference.…”
Section: Materials and Chemicalsmentioning
confidence: 99%